Regional disparities in steel production and restrictions to progress on global decarbonization: A cross-national analysis. (June 2022) - Wang, Peng; Zhao, Shen; Dai, Tao; Peng, Kun; Zhang, Qi; Li, Jiashuo; Chen, Wei-Qiang
Abstract: Steel production is one of few "difficult-to-decarbonize" sectors that requires strong decarbonization actions. However, the present focus is mainly limited to technical efforts, while regional disparities in steel production and its impacts on energy and carbon efficiency are rarely explored. By integrating environmental extended input-output analysis and material flow analysis, this study, as one of the first attempts, provides an analytical perspective to explore the regional emission performance of steel production across 44 countries and the rest 5 regions from 2000 to 2015, in which the physical indicators such as CO2 emission, energy use, and carbon intensity are compared. The results show that the CO2 emission associated with global steel production has increased by 2.5-fold from 2000 to 2015, and the global steel production has only increased by 1.9-fold, indicating a worsening environmental performance with emission intensity increasing from 2.1 tCO2 /t in 2000 to 2.8 tCO2 /t in 2015. This is closely linked to the historical changes in the geographical distribution of steel production as well as the faster increase of steel production in less efficient regions compared to that of more efficient regions. Despite the efficiency improvement in several nations, the carbon intensity of both developed (OECD, from 1.6 t CO2 /t to 2.3 t CO2/t) and developing nations (non-OECD: 2.7 t CO2 /t to 3.0 t CO2 /t) were increasing during the past decade. Thus, there is a need to incorporate regional disparities and inequalities in the designingglobal decarbonization strategies of steel and other heavy industrial sectors. Highlights: Steel production's energy and emission performance of 44 countries are quantified and compared. The CO2 intensity of global steel production kept increasing from 2000 to 2015. Regional disparities in steel production have key impacts on its global decarbonization progress. Key factors of CO2 emission from regional steel production were decomposed and explored. Continuing regional expansion and geographical transition of steel production may jeopardize climate targets.